Control of DSTATCOM using Sigmoidal Cost Based Logarithmic Algorithms in Grid Connected Distribution Systems - Bisht, Neeraj Singh; Arora, Ankita (2022 International Conference on Electronics and Renewable Systems (ICEARS), 2022)
This paper presents simulation of control of DSTATCOM for the application of power quality improvement in grid connected system using Sigmoid Cost framework based Least Mean Logarithmic Square and Least Logarithmic Absolute Difference algorithms. The DSTATCOM is used for compensating harmonic current and improving power factor at the point of common coupling. The performance of the algorithms is compared with the basic LMS algorithm. The results are shown under different loading conditions for settling time of DC bus voltage, THD in source voltage and current, weight convergence rate, oscillations under both steady state and dynamic conditions. The simulation, performance analysis and comparison are done using MATLAB/Simulink.